The hands raised to heaven. The social doctrine of the Church and refugees - Aparicio Malo, José Manuel (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
The dimensions of the refugee problem, the implications in terms of suffering for its protagonists, the associated cultural and political repercussions make it a challenge for Ethics and an urgent concern for the Social Doctrine of the Church. There is no systematic theological approach in a concrete document, but there are more than enough elements to configure a concrete and analytical posture as a proposal to the problem. The article aims at the critical approach of the reader towards the refugee crisis and the understanding of the positioning of the Catholic community, from the theological point of view.
Keywords: refugees; migrations; social moral doctrine; social doctrine of the Church